Exploring the health and wellbeing landscape at a third level institution - Emma S Cowley; Hannah R Goss; Caroline Mahon; Ciaran Dunne; Sarahjane Belton (Wellbeing, Space and Society)
In line with the Healthy Campus framework, this study explored the health, health literacy, and wellbeing landscape for students at an Irish third level institution using a participatory action research approach with the aim to identify potential need, and inform future health promotion action(s). Methods. This mixed-method study involved three phases; (1) a scoping review to audit what activities are currently available to support student health and wellbeing on campus, (2) assessment of students’ current health literacy using the Health Literacy Questionnaire, analysed using Cohen's d to investigate the magnitude of differences between student groups, (3) qualitative discussions with university stakeholders, analysed using reflexive thematic analysis, to provide greater understanding and context to the results of the previous phases. Results. The scoping review identified 151 activities on campus to support students’ holistic health, with the majority focused on individual support. Students’ health literacy scores were in line with the broader literature. A number of themes were identified within the qualitative data; i) the need for an ‘opt-in’ approach to support a health-integrated culture, ii) barriers and facilitators to health information, iii) the importance of ‘walking the walk’, iv) the specific university experience of 2022 as society emerged from Covid-19, and v) factors that influence student engagement. Conclusion. Insight into the participatory action approach undertaken in this study may be useful to inform other higher education institutions (HEIs) interested in undertaking similar work. Thorough description of the findings may also allow these to be transferred to other contexts. The findings of this study can help inform and direct the current university's, and potentially other HEIs, future actions in regards to enhancing the health and wellbeing of its stakeholders. To foster an authentic ‘Healthy Campus’, a whole-university approach is needed HEIs, supported by open dialogue between stakeholders and senior leadership commitment.